2017
DOI: 10.1111/vde.12474
|View full text |Cite
|
Sign up to set email alerts
|

Macrococcus canis and M. caseolyticus in dogs: occurrence, genetic diversity and antibiotic resistance

Abstract: This study gives some insights into the occurrence and genetic characteristics of antibiotic-resistant Macrococcus from dogs. Presence of M. canis in infection sites and resistance to antibiotics emphasized that more attention should be paid to this novel bacteria species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Macrococcus canis is the latest member described in the Macrococcus genus, which now contains a total of eight species ( M. caseolyticus , M. carouselicus , M. equipercicus , M. bovicus , M. brunensis , M. hajekii , M. lamae , and M. canis ( 1 ). M. canis has been found on the skin of healthy dogs and has also been associated with several types of skin- and mucosa-related infections ( 2 ). To our knowledge, it is the only Macrococcus species that produces hemolysis that is visible on sheep blood agar plates ( 1 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Macrococcus canis is the latest member described in the Macrococcus genus, which now contains a total of eight species ( M. caseolyticus , M. carouselicus , M. equipercicus , M. bovicus , M. brunensis , M. hajekii , M. lamae , and M. canis ( 1 ). M. canis has been found on the skin of healthy dogs and has also been associated with several types of skin- and mucosa-related infections ( 2 ). To our knowledge, it is the only Macrococcus species that produces hemolysis that is visible on sheep blood agar plates ( 1 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…However, a role for Macrococcus , in particular Macrococcus caseolyticus and Macrococcus canis in veterinary infections has become increasingly recognised. M. caseolyticus having been isolated from ovine abscesses [ 2 ], bovine mastitis [ 3 ], canine dermatitis [ 4 ], canine rhinitis [ 5 ] and canine otitis [ 3 ] with M. canis being linked to a range of canine infections [ 4 ]. Methicillin resistance has been described in both M. caseolyticus and M. canis .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of methicillin-resistant staphylococci, including methicillin-resistant Staphylococcus aureus (MRSA), mecA predominates, with mecC found in smaller numbers [ 9, 10 ]. Neither mecA or mecC have been reported in macrococci, instead the two other mec types, mecB and mecD , have been found in M. caseolyticus [ 3–5, 11 ] with mecB also being described in M. canis [ 4 ]. The relatedness of macrococci and staphylococci raises the potential for horizontal gene transfer between the genera and the spread of mecB- and mecD -mediated resistant to the more pathogenic staphylococci.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of coagulase-negative staphylococci, such as S. lugdunensis and S. schleiferi subsp. schleiferi, and of Macrococcus spp., can also cause confusion in laboratories that are looking for coagulase-positive bacteria (Cain et al, 2011;Gobeli Brawand et al, 2016;Cotting et al, 2017). Surprisingly, the idea that coagulase-negative staphylococci are non-pathogenic persists even though they are the most common cause of nosocomial bacteraemia in human hospitals (von Eiff et al, 2002;Becker et al, 2014) and are increasingly reported in animal infections (e.g.…”
Section: Pathogensmentioning
confidence: 99%